Integrated Perioperative Care: A Literature Review on the Roles of Nursing, Anesthesia, Radiology, and Laboratory Sciences in Supporting Complex Surgical Interventions - Ali Abdulkarim Al Rubh; Sami Abdulkareem Al Rubh; Baneen Mansoor Almarzouq; Hebah Abdulmajeed Altajir; Ebad Abdullah Hamed Althomali; Abdulaziz Hussain Alwadie; Hatem Ali Mohamed; Awwadh Raddad Abdullah Alrabie; Zuhair Mohammed G. Alzahrani; Rakan Dubian Faleh Albalwi; Nouf Mohammed Alsaleh; Modhi Salem Hubaylis Alotibi (International Journal of Medical Toxicology and Legal Medicine, 2024)
This article examines the integrated roles of nursing, anesthesia, radiology, and laboratory sciences in the perioperative care of patients undergoing complex surgical interventions. New medical treatments in recent years have created further needs concerning cohesive, multidisciplinary caring for the patients in the preoperative period of treatment, to which each professional field uniquely contributes. These nursing professionals prepare the patients preoperatively both physically and psychologically, assist in infection control and monitoring intra-operatively, and care for the patients post-operatively by educating and monitoring their recovery. The anesthesia teams make the preoperative assessments, manage anesthesia intra-operatively, and adjust the protocols in real time in keeping with patient responses to keep them stable and manage post-operative pain-a main determinant in recovery. These radiologists also support surgical teams with preoperative imaging that enables them to make detailed plans and assess risks, while intraoperative imaging provides additional real-time images to help guide the surgical team and confirm how accurately the procedure has been performed. Finally, radiology will provide input on early complication detection, enhancing patient safety by timely responses against possible issues. These laboratory scientists save lives through tests in the perioperative stages, starting initially with the preoperative assessment of health status, then the intraoperative stages by observing parameters that include blood gas and electrolyte levels, hence helping in informed decisions during surgery. Laboratory tests after surgery are important in assessing the progress of recovery and hence helping timely identification and management of complications. This review, therefore, establishes that the integration of such disciplines into effective perioperative care for such surgeries requires collaboration among health professionals in nursing, anesthesia, radiology, and laboratory sciences; it will ensure improvement in patient safety, a reduction in recovery time, and enhancement of the overall surgical outcomes. It takes a standardized protocol, training interprofessionally, and communication within a surgical team in order to advance the quality of care and patient outcomes for the perioperative services.